'It's Not a Gift When It Comes with Price': A Qualitative Study of Transactional Sex between UN Peacekeepers and Haitian Citizens. Issue 1 (20th August 2015) - Kolbe, Athena R.
Sexual exploitation of civilians by peacekeepers undermines the fragile stability established in post-conflict settings. Despite this, it continues to be an ongoing problem for peacekeeping missions worldwide. Efforts to respond to sexual exploitation and abuse (SEA) have focused on the establishment of rules prohibiting this behavior, condom distribution, and the training of peacekeepers before and during deployment. In an effort to further our understanding of the dynamics that surround SEA by peacekeepers, 231 Haitian citizens who have engaged in transactional sex with peacekeepers were interviewed about their opinions and experiences. Themes which emerged from these interviews included the triggering events or situations which facilitated engagement in transactional sex, the individual's understandings of their own experiences in relationship to cultural and social factors, sex as a strategy for filling unmet economic needs, and the differences between the relationships with peacekeepers and normal romantic relationships. Experiences with condom use, pregnancy, abuse, and barriers to reporting assault and harassment were also discussed.